Delignification of coconut husk by microwave assisted chemical pretreatment - Laghari, S.M. (American-Eurasian Network for Scientific Information, 2015)
Background: Coconut husk has the potential to be used as a source of alternative energy such as biofuel. Its high lignin content, however, poses difficulty to this use. Objective: To investigate the use of microwave assisted acidic and alkaline pretreatment methods to improve the characteristics of coconut husk for energy production. Results: It was found that microwave assisted sodium hydroxide pretreatment was most effective. Conclusion: 3.5 microwave assisted sodium hydroxide gave the best results in removing the lignin content and increasing the cellulose content. Â© 2015 AENSI Publisher All rights reserved.